Assessment of the Adherence to Public Relations Code of Ethics by Practitioners in Lagos State - Oduenyi, Chuddy Christian; Etumnu, Emeka Williams (Journal of Communication and Public Relations, 2025)
The study investigated practitioners' adherence to Lagos State, Nigeria's public relations code of ethics. The study was anchored on the two-way symmetrical model of PR and absolutist ethical theory. The investigation adopted an in-depth interview research method. The researchers reached out to 10 PR practitioners in Lagos. The researchers utilized the purposive sampling technique, and the interview guide was used as the data collection instrument. It was revealed that PR practitioners are vastly knowledgeable about the existing code of ethics governing PR practices in Lagos state and, by extension, Nigeria. Also, the result indicated that there is a low level of adherence to the code of ethics.  It was recommended that strict regulatory principles and actions be enforced on erring PR practitioners in Lagos state to deter others from breaking or twisting the code of ethics of PR practices and serve their agenda.